1991
DOI: 10.1016/0014-5793(91)80103-a
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the catalytic activity and oligomeric composition of enzymes in reversed micelles of surfactants in organic solvents

Abstract: The Phenomenon of the regulation of the catalytic activity of enzymes via changing their oligomeric composition in the system of reversed micelles of sodium bis(2‐ethylhexy)sulfosuccinate (AOT) in octane was studied using z‐chymotrypsin (CT) from bovine brain and alkaline phosphatase (AP) from calf intestinal mucosa. The dependences of the enzyme catalytic activity on the AOT hydration degree (W=[H2O][AOT]), the parameter determining the radius (r 4) of the inner cavity of micelles, usually represent the bell‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…The maximum of the catalytic activity was observed when the size of an inner micelle cavity was equal to that of the solubilized enzyme molecule [17,19,22,27,[29][30][31][32][33][36][37][38][39]. The supposition made on the basis of the results of studies of kinetics was confirmed by sedimentation analysis data.…”
Section: Introductionmentioning
confidence: 56%
See 2 more Smart Citations
“…The maximum of the catalytic activity was observed when the size of an inner micelle cavity was equal to that of the solubilized enzyme molecule [17,19,22,27,[29][30][31][32][33][36][37][38][39]. The supposition made on the basis of the results of studies of kinetics was confirmed by sedimentation analysis data.…”
Section: Introductionmentioning
confidence: 56%
“…In the case of calf intestinal mucosa alkaline phosphatase, two activity maxima have been observed when the radii of the AOT-isooctane-water reverse micellar inner cavity were approximately equal to the sizes of the monomeric and dimeric enzyme forms, respectively. The established widespread opinion that alkaline phosphatase possesses catalytic activity only in dimeric form was established from earlier attempts to separate the subunits of alkaline phosphatase using conventional methods (e.g., in urea solution) that resulted in a loss of the enzyme activity [29,30]. On the other hand, in the case of placental alkaline phosphatase, k cat is growing in an exponential way with w 0 , and no k cat maxima were found [40].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The activity maximum exists because the active enzyme conformation is maintained at specific micelle size that is optimal for a given enzyme. In case of several peaks, each one reflects the functioning of a separate catalytically active unit (Kabanov et al 1991). Thus, the presence of two maxima in the thylakoids implies the presence of at least two species bearing CA activity.…”
Section: Resultsmentioning
confidence: 99%
“…It is thought that the close contact between surfactant shell and enzyme helps maintain the latter in the catalytically active conformation. In the case of oligomeric enzymes, the dependence of kinetic parameters on w o shows peaks corresponding to each oligomeric form of an enzyme (49,(51)(52)(53)(54).…”
Section: Ph-dependent Oligomeric States Of Lipoamide Dehydrogenasementioning
confidence: 99%